Sound design for moving image from concept to realization - Scott-James, Kahra (Bloomsbury Academic, 2018)
"Contemporary soundtracks are often made up of hundreds of separate tracks, and thousands of individual sounds, including elements of dialogue, music and sound effects. As a result, many budding filmmakers find them a daunting prospect, and are tempted to leave sound to the last stages of post-production. 'Sound Design for Moving Image' offers a clear introduction to sound design theory and practice to help you integrate sound ideas into your productions."--Provided by publisher.